The Attractiveness of Quebec's Heritage Sites in The Era of Covid-19 - Longhi-Heredia, Sebastián Alberto; Marcotte, Pascale (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
UNESCO World Heritage site designation is an opportunity to achieve international status. Studies have demonstrated that many of these sites are major attractions to international visitors and first-time visitors. While Covid-19 has limited international mobility during 2020, this study aims to understand how those responsible for tourism and World Heritage sites have communicated the heritage of the Historic District of Old Quebec (Canada) to local and national visitors. To measure tourist attractiveness, the study analyzed publications posted on Instagram during the summer of 2020. Strategies for diffusion revealed an approach to enhance natural sites more than cultural heritage.